Halal hospitality for senior citizens in Malaysia: an analytical study from Islamic perspective - Fadhli, Ahmad Syarief; Fatah Yasin, Raudlotul Firdaus; Kamal Koh, Syamilah Heng (2019)
Malaysia will be an ageing nation by 2035, as reported by Department of Statistics Malaysia. Yet, the rapid increasing number of the elderly in tandem with the decrease in fertility and morbidity rate causes imbalance in the society’s structure. The elderly is often perceived negatively because of the stereotype and it affects their physical and mental health. This study tries to define the meaning of elderly from the Islamic perspective and attempts to provide the halal key concepts as guidelines to improve the hospitality after analysing the caretaking system in Malaysia using deductive and inductive method. This research hypothesized that the current caretaking system is progressing, but more drastic initiatives is needed to achieve a wholesome objective for elderly well-being from Islamic perspective.